Management of the area of deposition of industrial liquid effluents according to the fractal dimension of the soil - Spadotto, Anselmo José; Guerrini, Ivan Amaral; Tofoli, Camila Ambrosio; Feiden, Armin; Neumeister, Carsten (Universidade Federal de Minas Gerais, 2000)
The industries that deposit liquid effluents in the soil have the concern that this liquid does not reach the water table and, also, do not form great basins located in open pits. In the absence of any other method of immediate control, the most suitable solution for the liquid deposition is allowing only superficial infiltration of the liquid residue in the area, in a way that it does not reach the water table. In some cases, it could be adopted double or triple's soil layers. For example, a first layer would absorb liquids at a higher rate and a second one would retain and incorporate the pollutants, until those pollutants could be mechanically removed. That simulation could be made through a certain combination of soils with their appropriate fractals dimensions. The soil structure has relationship with the infiltration rate of liquids into his interior, and the fractal dimension could be used as an important tool for the knowledge of that structure. The objective of this work is to study the of infiltration rate of water in two types of soils to supply subsidies to the management of industrial effluents. For the soil with fractal dimension 2.70+0.002, in a time of 50 minutes, the front watering height was of 15 cm and, for the soil with fractal dimension 2.49+0.001, in the same time, the front watering height was of 37 cm.
Gestão da área de deposição de efluentes líquidos industriais com base na dimensão fractal do solo
Keywords: Effluent; Fractal; Soil; Efluente; Fractais; Solo